1985
DOI: 10.1677/joe.0.1050227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibition of prostaglandin synthesis on cervical softening and uterine activity during ovine parturition resulting from progesterone withdrawal induced by epostane

Abstract: The effects of an inhibitor of 3 beta-hydroxysteroid dehydrogenase (epostane) on uterine activity and cervical softening have been studied in eight sheep during late pregnancy. Treatment with epostane led to a rapid decline in the concentration of progesterone measured in utero-ovarian venous plasma, to less than 10% of the pretreatment value within 30 min of bolus injection. This was followed by a significant (P less than 0.02) increase in the concentrations of metabolites of prostaglandins E and F in utero-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

1987
1987
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 18 publications
2
10
1
Order By: Relevance
“…The rapid sustained drop in maternal plasma progesterone concentrations after epostane con¬ firmed previous observations with trilostane and epostane on pregnant sheep (Taylor et al, 1982;Jenkin & Thorburn, 1984;Ledger et al, 1985). This persistent inhibition of placental 3ß-HSD is difficult to explain and is in marked contrast to the action of epostane in two other species.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The rapid sustained drop in maternal plasma progesterone concentrations after epostane con¬ firmed previous observations with trilostane and epostane on pregnant sheep (Taylor et al, 1982;Jenkin & Thorburn, 1984;Ledger et al, 1985). This persistent inhibition of placental 3ß-HSD is difficult to explain and is in marked contrast to the action of epostane in two other species.…”
Section: Discussionsupporting
confidence: 80%
“…A feature of the rapid drop in circulating progesterone in this and earlier studies was the equally fast increase in maternal plasma PGFM concentration (Taylor et al, 1982;Jenkin & Thorburn, 1984;Ledger et al, 1985). This raises the question of whether a rise in oestrogen is in fact required for the induction of uterine PGF production in the sheep: a view which is widely held (Liggins et al, 1973; Thorburn & Challis, 1979).…”
Section: Discussionmentioning
confidence: 49%
“…The present study and other reports on endometrial expiants of nonpregnant sheep and endometrial epithelial cultures of cows (Horn et (Vallet et al, 1990;Larcher et al, 1995;Wathes et al, 1996b (Breton et al, 1996) (Vallet et al, 1990;Wathes et al, 1996b (Ledger et al, 1985;Li et al, 1991) and similar experiments with RU486 in rats showed that treatment resulted in an increase in uterine oxytocin receptor expression (Fang et al, 1996(Fang et al, , 1997. In the present study, disruption of the progesterone-dominated environment for as little as 4 h was sufficient to remove the inhibitory effect of progesterone.…”
Section: Progesterone Radioimmunoassaysupporting
confidence: 83%
“…Cervical compliance is certainly affected by the maternal hormonal environment (Fitzpatrick, 1977). In the sheep a sudden drop in progesterone in the absence of any rise in oestrogen will induce cervical ripening within a few hours (Ledger, Webster, Anderson & Turnbull, 1985) while oestrogen alone will also elicit softening (Fitzpatrick & Dobson, 1981). That prostaglandins are the primary factors in cervical ripening is shown by the effectiveness of exogenous PGE and by the inhibitory action of PG synthetase inhibitors (Fitzpatrick & Dobson, 1981;Ledger, Ellwood & Taylor, 1983).…”
Section: Maternal Changesmentioning
confidence: 99%